A 6A double aluminum foil shielded network cable and its preparation method

By using multiple pair-stranded wire contacts and aluminum foil shielding layers in the shielded network cable and using modified polymer materials, the shortcomings of existing shielded network cables in terms of attenuation performance, mechanical properties, cold resistance and corrosion resistance are solved, and higher communication quality is achieved.

CN118711896BActive Publication Date: 2025-03-14ZHUOSHENG (GUANGDONG) CABLE IND CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410876329.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-02
Publication Date
2025-03-14
Estimated Expiration
2044-07-02

AI Technical Summary

Technical Problem

The existing shielded network cables have shortcomings in attenuation performance, mechanical properties, cold resistance and corrosion resistance, which affects the communication quality.

Method used

The 6A double aluminum foil shielded mesh wire is used to contact each other through multiple pairs of twisted wires and contact with the ground wire to form a cable main body, and wrap the overall shielding layer and the outer cavity around the outer cavity, the insulating layer and the outer cavity are made of modified polymer material.

Benefits of technology

It significantly improves the mechanical properties and attenuation properties of the network cable, improves cold resistance and corrosion resistance, and improves communication quality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004923147740000161
    Figure BDA0004923147740000161
  • Figure BDA0004923147740000171
    Figure BDA0004923147740000171
  • Figure BDA0004923147740000191
    Figure BDA0004923147740000191
Patent Text Reader

Abstract

The present invention relates to the technical field of shielded network cables, and specifically discloses a 6A double aluminum foil shielded network cable, the shielded network cable comprises a cable body, the cable body comprises a plurality of twisted pairs; each twisted pair comprises two core wires twisted together and a shielding layer sequentially wrapped around the two core wires; each core wire comprises a conductor and an insulating layer wrapped around the conductor. The double aluminum foil shielded network cable of the present invention adopts a plurality of twisted pairs of wires that are in contact with each other, and the plurality of twisted pairs of wires are in contact with a ground wire to form a cable body, a total shielding layer is coated around the outer periphery of the cable body, and an outer sheath is arranged around the outer periphery of the total shielding layer, and the outer sheath and the insulating layer are made of modified polymer materials, thereby optimizing the overall mechanical properties of the network cable product, the coordinated improvement of the attenuation performance, and the cold resistance and corrosion resistance stability are remarkable.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of shielded network cables, and in particular to a 6A double aluminum foil shielded network cable and a preparation method thereof. Background Art

[0002] Shielded network cable is a multimedia cable for transmitting data, voice and other information communication services. It is widely used in broadband access projects such as broadband user premises networks. Its quality is directly related to the transmission quality of information communication. The parameters of shielded network cables have been greatly improved compared with the old standard network cables, and the transmission frequency has also been extended to 500MHz. The length limit of the double-shielded network cable channel is 100m (meters). This distance is mainly suitable for high-speed wiring of large enterprises. The transmission speed can reach 10Gbp / s (gigabits per second). The 10Gbp / s transmission speed strictly requires the CAT6A network cable wiring performance to be as high as 500MHz (megahertz) test frequency.

[0003] Existing shielded network cables use conventional production processes and product structures, with poor attenuation performance, which easily affects communication quality. At the same time, the mechanical properties and attenuation performance of the product are difficult to coordinate and improve, and the cold and corrosion resistance are poor, which further limits the product's efficiency. Summary of the invention

[0004] In view of the defects of the prior art, the purpose of the present invention is to provide a 6A double aluminum foil shielded network cable and a preparation method thereof to solve the problems raised in the above background technology.

[0005] The present invention solves the technical problem by adopting the following technical solution:

[0006] The present invention provides a 6A double aluminum foil shielded network cable, the shielded network cable comprises a cable body, the cable body comprises a plurality of twisted pairs;

[0007] Each twisted pair wire includes two core wires twisted together and a shielding layer wrapped around the two core wires in sequence; each core wire includes a conductor and an insulating layer wrapped around the conductor;

[0008] The cable body also includes a ground wire, and on a cross section of the cable body, the plurality of twisted pairs are evenly distributed around the ground wire; the plurality of twisted pairs are in contact with each other, and the plurality of twisted pairs are in contact with the ground wire;

[0009] Also included is an overall shielding layer wrapped around the periphery of the cable body;

[0010] The shielding layer and the overall shielding layer are both aluminum foil layers; the network cable also includes an outer sheath sequentially wrapped around the outer periphery of the overall shielding layer;

[0011] The insulating layer and the outer sheath are both made of modified polymer materials, wherein the modified polymer materials include the following raw materials in parts by weight:

[0012] 35-45 parts of base material, 7-11 parts of an improving agent based on flaky talc, 3-7 parts of a silane coupling agent, 4-6 parts of a replenishing and improving agent, 1-3 parts of a crosslinking agent, 2-5 parts of an antioxidant, 1-3 parts of stearic acid, and 1-3 parts of carbon black;

[0013] The base material is prepared from ethylene-vinyl acetate copolymer, linear low-density polyethylene and ethylene-propylene rubber in a weight ratio of 4:1:2.

[0014] Preferably, the conductor is made of copper wire, and the thickness of the aluminum foil layer is 0.5-0.7 mm;

[0015] The silane coupling agent is silane coupling agent KH560;

[0016] The cross-linking agent is dicumyl peroxide; the antioxidant is 2,6-di-tert-butyl-p-cresol;

[0017] The melting index of ethylene-vinyl acetate copolymer is 4-7g / 10min, and the mass content of vinyl acetate in ethylene-vinyl acetate copolymer is 35-40%; the melting index of ethylene-propylene rubber is 2-5g / 10min; and the melting index of linear low-density polyethylene is 10-15g / 10min.

[0018] Preferably, the preparation method of the enhancement agent based on flaky talc is:

[0019] S01: Stir and mix the flaky talc powder in a sufficient amount of 5% by mass potassium permanganate solution, then filter and dry;

[0020] The dried flaky talc, the sodium dodecylbenzene sulfonate solution and the phosphate buffer solution are mixed in a weight ratio of 2:5:1 to obtain a flaky talc agent;

[0021] S02: 1-3 parts of nano silica sol, 2-5 parts of carboxymethyl cellulose and 4-6 parts of ethanol solvent are mixed to obtain an additive solution;

[0022] The added liquid and talc powder are subjected to ultrasonic modification treatment in a weight ratio of 2:5, and after the ultrasonic treatment is completed, the talc powder is filtered and dried to obtain a talc powder modifier;

[0023] S03: The flaky talc modifier and the synergist are mixed in a weight ratio of 7:5 and ball-milled at a speed of 1500 r / min for 2 h. After the ball-milling is completed, the mixture is washed with water and dried to obtain a synergist adjusted based on the flaky talc.

[0024] Preferably, the mass fraction of the sodium dodecylbenzene sulfonate solution is 4-7%; and the pH value of the phosphate buffer solution is 5.0-5.5.

[0025] Preferably, the ultrasonic power of the ultrasonic modification treatment is 450-550W, and the ultrasonic time is 20-30min.

[0026] Preferably, the synergistic agent comprises the following raw materials in parts by weight:

[0027] 10-15 parts of nano-mica powder, 2-5 parts of chitosan solution, 1-3 parts of yttrium oxide, 2-4 parts of silicon carbide whiskers and 3-6 parts of sodium lignin sulfonate solution.

[0028] Preferably, the mass fraction of the chitosan solution is 2-5%; the mass fraction of the sodium lignin sulfonate solution is 4-7%.

[0029] Preferably, the preparation method of the tonic and tonifying agent is:

[0030] S11: treating the glass fiber with proton irradiation, wherein the irradiation power is 350-400 W and the irradiation time is 10-20 min. After the irradiation is completed, irradiated glass fiber is obtained;

[0031] S12: fully blending 4-7 parts of irradiated glass fiber, 2-5 parts of 5% by mass lanthanum nitrate solution, 1-3 parts of urea, 1-2 parts of silane coupling agent KH550 and 3-5 parts of 7% by mass sodium citrate solution to obtain a glass fiber modified solution;

[0032] S13: immersing the hydroxyapatite in a sufficient amount of sodium silicate solution with a mass fraction of 5-7%, filtering and drying after the immersion is completed to obtain dry hydroxyapatite, and mixing the dry hydroxyapatite and the glass fiber modified liquid in a weight ratio of 5:3 for ball milling. After the ball milling is completed, filtering and drying are performed to obtain a replenishing and tonifying agent.

[0033] Preferably, the immersion power of the immersion treatment is 350-400W, and the immersion time is 10-20min; the ball milling speed of the mixed ball milling treatment is 1000-1500r / min, and the ball milling is 2h.

[0034] The present invention also provides a method for preparing a 6A double aluminum foil shielded network cable, comprising the following steps:

[0035] Step 1: The base material, the effect agent adjusted based on flaky talc, the silane coupling agent, the tonic agent, the crosslinking agent, the antioxidant, the stearic acid and the carbon black are uniformly blended, and then kneaded at 110° C. for 5 minutes, and then extruded and granulated in a twin-screw extruder at an extrusion temperature of 135° C. to obtain a modified polymer material;

[0036] Step 2: An insulating layer and an outer sheath are made of modified polymer materials, and a core wire is made of a conductor and an insulating layer wrapped around the conductor, and each twisted pair is made of two core wires twisted together and a shielding layer wrapped around the two core wires in sequence;

[0037] Step three: a cable body is formed by making multiple twisted pairs contact each other and multiple twisted pairs contact the ground wire, a total shielding layer is covered on the periphery of the cable body, and an outer sheath is arranged on the periphery of the total shielding layer to form the 6A double aluminum foil shielded network cable of the present invention.

[0038] Compared with the prior art, the present invention has the following beneficial effects:

[0039] The double aluminum foil shielded network cable of the present invention adopts a plurality of twisted pairs of wires that are in contact with each other and the plurality of twisted pairs of wires are in contact with a ground wire to form a cable body, a total shielding layer is coated on the outer periphery of the cable body and an outer sheath is arranged on the outer periphery of the total shielding layer, and the outer sheath and the insulating layer are made of modified polymer materials, so as to optimize the overall mechanical properties and attenuation performance of the network cable product, and achieve remarkable cold resistance and corrosion resistance stability; the modified polymer material is prepared by using base material, cross-linking agent, antioxidant, stearic acid and other raw materials, and by adding an effect-enhancing agent and a tonic agent adjusted by flaky talcum powder, The performance of the product is further improved by using the synergistic effect of the two. The flaky talc modifier is based on the potassium permanganate treatment of flaky talc to optimize the active performance of the flaky talc. The flaky talc agent is obtained by mixing talc with sodium dodecylbenzene sulfonate solution and phosphate buffer solution, and the additive liquid is fully mixed with nano-silica sol, carboxymethyl cellulose and ethanol solvent. The additive liquid is used to coordinate and improve the flaky talc agent, optimize the active performance and interface performance of talc, thereby improving the synergistic effect of the flaky talc modifier and the synergistic effect modifier. The synergistic effect is improved by mixing nano mica powder, chitosan solution, yttrium oxide, silicon carbide whiskers and sodium lignin sulfonate solution. The lamellar activity and dispersion of nano mica powder are improved by combining lamellar nano mica powder with chitosan solution, yttrium oxide and sodium lignin sulfonate solution. At the same time, silicon carbide whiskers are used to coordinate lamellar nano mica powder. The whisker body with whisker-like structure coordinates the lamellar nano mica powder. The mechanical properties and attenuation performance of the product are enhanced and improved by assembling and matching the lamellar nano mica powder and flaky talc powder. Improve the stability of the product; the replenishing and adjusting agent adopts glass fiber through proton irradiation to improve the activity efficiency of the glass fiber, and then fully mixes lanthanum nitrate solution, urea and silane coupling agent KH550 and 7% sodium citrate solution by mass to obtain glass fiber modified liquid, and the needle-like structure of the glass fiber is matched with the raw materials in the glass fiber modified liquid, and the hydroxyapatite is coordinated by the blending improvement and optimization of the raw materials, and the performance effect of the glass fiber reinforcement system is further enhanced by the point structure of hydroxyapatite and the needle-like structure. DETAILED DESCRIPTION

[0040] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0041] A 6A double aluminum foil shielded network cable of this embodiment, the shielded network cable includes a cable body, and the cable body includes a plurality of twisted pairs;

[0042] Each twisted pair wire includes two core wires twisted together and a shielding layer wrapped around the two core wires in sequence; each core wire includes a conductor and an insulating layer wrapped around the conductor;

[0043] The cable body also includes a ground wire, and on a cross section of the cable body, the plurality of twisted pairs are evenly distributed around the ground wire; the plurality of twisted pairs are in contact with each other, and the plurality of twisted pairs are in contact with the ground wire;

[0044] Also included is an overall shielding layer wrapped around the periphery of the cable body;

[0045] The shielding layer and the overall shielding layer are both aluminum foil layers; the network cable also includes an outer sheath sequentially wrapped around the outer periphery of the overall shielding layer;

[0046] The insulating layer and the outer sheath are both made of modified polymer materials, wherein the modified polymer materials include the following raw materials in parts by weight:

[0047] 35-45 parts of base material, 7-11 parts of an improving agent based on flaky talc, 3-7 parts of a silane coupling agent, 4-6 parts of a replenishing and improving agent, 1-3 parts of a crosslinking agent, 2-5 parts of an antioxidant, 1-3 parts of stearic acid, and 1-3 parts of carbon black;

[0048] The base material is prepared from ethylene-vinyl acetate copolymer, linear low-density polyethylene and ethylene-propylene rubber in a weight ratio of 4:1:2.

[0049] The conductor of this embodiment is made of copper wire, and the thickness of the aluminum foil layer is 0.5-0.7mm;

[0050] The silane coupling agent is silane coupling agent KH560;

[0051] The cross-linking agent is dicumyl peroxide; the antioxidant is 2,6-di-tert-butyl-p-cresol;

[0052] The melting index of ethylene-vinyl acetate copolymer is 4-7g / 10min, and the mass content of vinyl acetate in ethylene-vinyl acetate copolymer is 35-40%; the melting index of ethylene-propylene rubber is 2-5g / 10min; and the melting index of linear low-density polyethylene is 10-15g / 10min.

[0053] The preparation method of the effect-enhancing agent based on flaky talcum powder adjustment in this embodiment is:

[0054] S01: Stir and mix the flaky talc powder in a sufficient amount of 5% potassium permanganate solution, then filter and dry;

[0055] The dried flaky talc, the sodium dodecylbenzene sulfonate solution and the phosphate buffer solution are mixed in a weight ratio of 2:5:1 to obtain a flaky talc agent;

[0056] S02: 1-3 parts of nano silica sol, 2-5 parts of carboxymethyl cellulose and 4-6 parts of ethanol solvent are mixed to obtain an additive solution;

[0057] The liquid and talc powder are added in a weight ratio of 2:5 and subjected to ultrasonic modification. After the ultrasonic modification is completed, the talc powder is filtered and dried to obtain a talc powder modifier.

[0058] S03: The flaky talc modifier and the synergist are mixed in a weight ratio of 7:5 and ball-milled at a speed of 1500 r / min for 2 h. After the ball-milling is completed, the mixture is washed with water and dried to obtain a synergist adjusted based on the flaky talc.

[0059] The mass fraction of the sodium dodecylbenzenesulfonate solution in this embodiment is 4-7%; the pH value of the phosphate buffer solution is 5.0-5.5.

[0060] The ultrasonic power of the ultrasonic modification treatment in this embodiment is 450-550W, and the ultrasonic time is 20-30min.

[0061] The effective synergistic agent of this embodiment includes the following raw materials in parts by weight:

[0062] 10-15 parts of nano-mica powder, 2-5 parts of chitosan solution, 1-3 parts of yttrium oxide, 2-4 parts of silicon carbide whiskers and 3-6 parts of sodium lignin sulfonate solution.

[0063] The mass fraction of the chitosan solution in this embodiment is 2-5%; the mass fraction of the sodium lignin sulfonate solution is 4-7%.

[0064] Preparation method of the tonic and tonifying agent of this embodiment:

[0065] S11: treating the glass fiber with proton irradiation, wherein the irradiation power is 350-400 W and the irradiation time is 10-20 min. After the irradiation is completed, irradiated glass fiber is obtained;

[0066] S12: fully blending 4-7 parts of irradiated glass fiber, 2-5 parts of 5% by mass lanthanum nitrate solution, 1-3 parts of urea, 1-2 parts of silane coupling agent KH550 and 3-5 parts of 7% by mass sodium citrate solution to obtain a glass fiber modified solution;

[0067] S13: immersing the hydroxyapatite in a sufficient amount of sodium silicate solution with a mass fraction of 5-7%, filtering and drying after the immersion is completed to obtain dry hydroxyapatite, and mixing the dry hydroxyapatite and the glass fiber modified liquid in a weight ratio of 5:3 for ball milling. After the ball milling is completed, filtering and drying are performed to obtain a replenishing and tonifying agent.

[0068] The immersion power of the immersion treatment in this embodiment is 350-400W, and the immersion time is 10-20min; the ball milling speed of the mixed ball milling treatment is 1000-1500r / min, and the ball milling is 2h.

[0069] A method for preparing a 6A double aluminum foil shielded network cable in this embodiment includes the following steps:

[0070] Step 1: The base material, the effect agent adjusted based on flaky talc, the silane coupling agent, the tonic agent, the crosslinking agent, the antioxidant, the stearic acid and the carbon black are uniformly blended, and then kneaded at 110° C. for 5 minutes, and then extruded and granulated in a twin-screw extruder at an extrusion temperature of 135° C. to obtain a modified polymer material;

[0071] Step 2: An insulating layer and an outer sheath are made of modified polymer materials, and a core wire is made of a conductor and an insulating layer wrapped around the conductor, and each twisted pair is made of two core wires twisted together and a shielding layer wrapped around the two core wires in sequence;

[0072] Step three: a cable body is formed by making multiple twisted pairs contact each other and multiple twisted pairs contact the ground wire, a total shielding layer is covered on the periphery of the cable body, and an outer sheath is arranged on the periphery of the total shielding layer to form the 6A double aluminum foil shielded network cable of the present invention.

[0073] Example 1.

[0074] A 6A double aluminum foil shielded network cable of this embodiment, the shielded network cable includes a cable body, and the cable body includes a plurality of twisted pairs;

[0075] Each twisted pair wire includes two core wires twisted together and a shielding layer wrapped around the two core wires in sequence; each core wire includes a conductor and an insulating layer wrapped around the conductor;

[0076] The cable body also includes a ground wire, and on a cross section of the cable body, the plurality of twisted pairs are evenly distributed around the ground wire; the plurality of twisted pairs are in contact with each other, and the plurality of twisted pairs are in contact with the ground wire;

[0077] Also included is an overall shielding layer wrapped around the periphery of the cable body;

[0078] The shielding layer and the overall shielding layer are both aluminum foil layers; the network cable also includes an outer sheath sequentially wrapped around the outer periphery of the overall shielding layer;

[0079] The insulating layer and the outer sheath are both made of modified polymer materials, wherein the modified polymer materials include the following raw materials in parts by weight:

[0080] 35 parts of base material, 7 parts of an improving agent based on flaky talc, 3 parts of a silane coupling agent, 4 parts of a replenishing and improving agent, 1 part of a crosslinking agent, 2 parts of an antioxidant, 1 part of stearic acid, and 1 part of carbon black;

[0081] The base material is prepared from ethylene-vinyl acetate copolymer, linear low-density polyethylene and ethylene-propylene rubber in a weight ratio of 4:1:2.

[0082] The conductor in this embodiment is made of copper wire, and the thickness of the aluminum foil layer is 0.5 mm;

[0083] The silane coupling agent is silane coupling agent KH560;

[0084] The cross-linking agent is dicumyl peroxide; the antioxidant is 2,6-di-tert-butyl-p-cresol;

[0085] The melting index of ethylene-vinyl acetate copolymer is 4g / 10min, and the mass content of vinyl acetate in ethylene-vinyl acetate copolymer is 35%; the melting index of ethylene-propylene rubber is 2g / 10min; and the melting index of linear low-density polyethylene is 10g / 10min.

[0086] The preparation method of the effect-enhancing agent based on flaky talcum powder adjustment in this embodiment is:

[0087] S01: Stir and mix the flaky talc powder in a sufficient amount of 5% by mass potassium permanganate solution, then filter and dry;

[0088] The dried flaky talc, the sodium dodecylbenzene sulfonate solution and the phosphate buffer solution are mixed in a weight ratio of 2:5:1 to obtain a flaky talc agent;

[0089] S02: 1 part of nano silica sol, 2 parts of carboxymethyl cellulose and 4 parts of ethanol solvent are mixed to obtain an additive solution;

[0090] The liquid and talc powder are added in a weight ratio of 2:5 and subjected to ultrasonic modification. After the ultrasonic modification is completed, the talc powder is filtered and dried to obtain a talc powder modifier.

[0091] S03: The flaky talc modifier and the synergist are mixed in a weight ratio of 7:5 and ball-milled at a speed of 1500 r / min for 2 h. After the ball-milling is completed, the mixture is washed with water and dried to obtain a synergist adjusted based on the flaky talc.

[0092] The mass fraction of the sodium dodecylbenzenesulfonate solution in this embodiment is 4%; the pH value of the phosphate buffer solution is 5.0.

[0093] The ultrasonic power of the ultrasonic modification treatment in this embodiment is 450 W, and the ultrasonic time is 20 min.

[0094] The effective synergistic agent of this embodiment includes the following raw materials in parts by weight:

[0095] 10 parts of nano-mica powder, 2 parts of chitosan solution, 1 part of yttrium oxide, 2 parts of silicon carbide whiskers and 3 parts of sodium lignin sulfonate solution.

[0096] The mass fraction of the chitosan solution in this embodiment is 2%; the mass fraction of the sodium lignin sulfonate solution is 4%.

[0097] Preparation method of the tonic and tonifying agent of this embodiment:

[0098] S11: treating the glass fiber with proton irradiation, wherein the irradiation power is 350 W and the irradiation time is 10 min. After the irradiation is completed, an irradiated glass fiber is obtained;

[0099] S12: fully blending 4 parts of irradiated glass fibers, 2 parts of 5% by mass lanthanum nitrate solution, 1 part of urea, 1 part of silane coupling agent KH550 and 3 parts of 7% by mass sodium citrate solution to obtain a glass fiber modified solution;

[0100] S13: immersing the hydroxyapatite in a sufficient amount of sodium silicate solution with a mass fraction of 5%, filtering and drying after the immersion is completed to obtain dry hydroxyapatite, and mixing the dry hydroxyapatite and the glass fiber modified liquid in a weight ratio of 5:3 for ball milling. After the ball milling is completed, filtering and drying are performed to obtain a replenishing and tonifying agent.

[0101] The immersion power of the immersion treatment in this embodiment is 350W, and the immersion time is 10 minutes; the ball milling speed of the mixed ball milling treatment is 1000r / min, and the ball milling is 2h.

[0102] A method for preparing a 6A double aluminum foil shielded network cable in this embodiment includes the following steps:

[0103] Step 1: The base material, the effect agent adjusted based on flaky talc, the silane coupling agent, the tonic agent, the crosslinking agent, the antioxidant, the stearic acid and the carbon black are uniformly blended, and then kneaded at 110° C. for 5 minutes, and then extruded and granulated in a twin-screw extruder at an extrusion temperature of 135° C. to obtain a modified polymer material;

[0104] Step 2: An insulating layer and an outer sheath are made of modified polymer materials, and a core wire is made of a conductor and an insulating layer wrapped around the conductor, and each twisted pair is made of two core wires twisted together and a shielding layer wrapped around the two core wires in sequence;

[0105] Step three: a cable body is formed by making multiple twisted pairs contact each other and multiple twisted pairs contact the ground wire, a total shielding layer is covered on the periphery of the cable body, and an outer sheath is arranged on the periphery of the total shielding layer to form the 6A double aluminum foil shielded network cable of the present invention.

[0106] Example 2.

[0107] A 6A double aluminum foil shielded network cable of this embodiment, the shielded network cable includes a cable body, and the cable body includes a plurality of twisted pairs;

[0108] Each twisted pair wire includes two core wires twisted together and a shielding layer wrapped around the two core wires in sequence; each core wire includes a conductor and an insulating layer wrapped around the conductor;

[0109] The cable body also includes a ground wire, and on a cross section of the cable body, the plurality of twisted pairs are evenly distributed around the ground wire; the plurality of twisted pairs are in contact with each other, and the plurality of twisted pairs are in contact with the ground wire;

[0110] Also included is an overall shielding layer wrapped around the periphery of the cable body;

[0111] The shielding layer and the overall shielding layer are both aluminum foil layers; the network cable also includes an outer sheath sequentially wrapped around the outer periphery of the overall shielding layer;

[0112] The insulating layer and the outer sheath are both made of modified polymer materials, wherein the modified polymer materials include the following raw materials in parts by weight:

[0113] 45 parts of base material, 11 parts of an improving agent based on flaky talc, 7 parts of a silane coupling agent, 6 parts of a replenishing and improving agent, 3 parts of a crosslinking agent, 5 parts of an antioxidant, 3 parts of stearic acid, and 3 parts of carbon black;

[0114] The base material is prepared from ethylene-vinyl acetate copolymer, linear low-density polyethylene and ethylene-propylene rubber in a weight ratio of 4:1:2.

[0115] The conductor of this embodiment is made of copper wire, and the thickness of the aluminum foil layer is 0.7 mm;

[0116] The silane coupling agent is silane coupling agent KH560;

[0117] The cross-linking agent is dicumyl peroxide; the antioxidant is 2,6-di-tert-butyl-p-cresol;

[0118] The melting index of ethylene-vinyl acetate copolymer is 7g / 10min, and the mass content of vinyl acetate in ethylene-vinyl acetate copolymer is 40%; the melting index of ethylene-propylene rubber is 5g / 10min; and the melting index of linear low-density polyethylene is 10-15g / 10min.

[0119] The preparation method of the effect-enhancing agent based on flaky talcum powder adjustment in this embodiment is:

[0120] S01: Stir and mix the flaky talc powder in a sufficient amount of 5% by mass potassium permanganate solution, then filter and dry;

[0121] The dried flaky talc, the sodium dodecylbenzene sulfonate solution and the phosphate buffer solution are mixed in a weight ratio of 2:5:1 to obtain a flaky talc agent;

[0122] S02: 3 parts of nano silica sol, 5 parts of carboxymethyl cellulose and 6 parts of ethanol solvent are fully mixed to obtain an additive solution;

[0123] The added liquid and talc powder are subjected to ultrasonic modification treatment in a weight ratio of 2:5, and after the ultrasonic treatment is completed, the talc powder is filtered and dried to obtain a talc powder modifier;

[0124] S03: The flaky talc modifier and the synergist are mixed in a weight ratio of 7:5 and ball-milled at a speed of 1500 r / min for 2 h. After the ball-milling is completed, the mixture is washed with water and dried to obtain a synergist adjusted based on the flaky talc.

[0125] The mass fraction of the sodium dodecylbenzenesulfonate solution in this embodiment is 7%; the pH value of the phosphate buffer solution is 5.5.

[0126] The ultrasonic power of the ultrasonic modification treatment in this embodiment is 550W, and the ultrasonic time is 30min.

[0127] The effective synergistic agent of this embodiment includes the following raw materials in parts by weight:

[0128] 15 parts of nano-mica powder, 5 parts of chitosan solution, 3 parts of yttrium oxide, 4 parts of silicon carbide whiskers and 6 parts of sodium lignin sulfonate solution.

[0129] The mass fraction of the chitosan solution in this embodiment is 5%; the mass fraction of the sodium lignin sulfonate solution is 7%.

[0130] Preparation method of the tonic and tonifying agent of this embodiment:

[0131] S11: treating the glass fiber with proton irradiation, with an irradiation power of 400 W and an irradiation time of 20 min. After the irradiation is completed, an irradiated glass fiber is obtained;

[0132] S12: 7 parts of irradiated glass fibers, 5 parts of 5% by mass lanthanum nitrate solution, 3 parts of urea, 2 parts of silane coupling agent KH550 and 5 parts of 7% by mass sodium citrate solution are fully mixed to obtain a glass fiber modified solution;

[0133] S13: immersing the hydroxyapatite in a sufficient amount of sodium silicate solution with a mass fraction of 7%, filtering and drying after the immersion is completed to obtain dry hydroxyapatite, and mixing the dry hydroxyapatite and the glass fiber modified liquid in a weight ratio of 5:3 for ball milling. After the ball milling is completed, filtering and drying are performed to obtain a replenishing and tonifying agent.

[0134] The immersion power of the immersion treatment in this embodiment is 400W, and the immersion time is 20min; the ball milling speed of the mixed ball milling treatment is 1500r / min, and the ball milling is 2h.

[0135] A method for preparing a 6A double aluminum foil shielded network cable in this embodiment includes the following steps:

[0136] Step 1: The base material, the effect agent adjusted based on flaky talc, the silane coupling agent, the tonic agent, the crosslinking agent, the antioxidant, the stearic acid and the carbon black are uniformly blended, and then kneaded at 110° C. for 5 minutes, and then extruded and granulated in a twin-screw extruder at an extrusion temperature of 135° C. to obtain a modified polymer material;

[0137] Step 2: An insulating layer and an outer sheath are made of modified polymer materials, and a core wire is made of a conductor and an insulating layer wrapped around the conductor, and each twisted pair is made of two core wires twisted together and a shielding layer wrapped around the two core wires in sequence;

[0138] Step three: a cable body is formed by making multiple twisted pairs contact each other and multiple twisted pairs contact the ground wire, a total shielding layer is covered on the periphery of the cable body, and an outer sheath is arranged on the periphery of the total shielding layer to form the 6A double aluminum foil shielded network cable of the present invention.

[0139] Example 3.

[0140] A 6A double aluminum foil shielded network cable of this embodiment, the shielded network cable includes a cable body, and the cable body includes a plurality of twisted pairs;

[0141] Each twisted pair wire includes two core wires twisted together and a shielding layer wrapped around the two core wires in sequence; each core wire includes a conductor and an insulating layer wrapped around the conductor;

[0142] The cable body also includes a ground wire, and on a cross section of the cable body, the plurality of twisted pairs are evenly distributed around the ground wire; the plurality of twisted pairs are in contact with each other, and the plurality of twisted pairs are in contact with the ground wire;

[0143] Also included is an overall shielding layer wrapped around the periphery of the cable body;

[0144] The shielding layer and the overall shielding layer are both aluminum foil layers; the network cable also includes an outer sheath sequentially wrapped around the outer periphery of the overall shielding layer;

[0145] The insulating layer and the outer sheath are both made of modified polymer materials, wherein the modified polymer materials include the following raw materials in parts by weight:

[0146] 40 parts of base material, 8.5 parts of an improving agent based on flaky talc, 5 parts of a silane coupling agent, 5 parts of a replenishing and improving agent, 2 parts of a crosslinking agent, 3.5 parts of an antioxidant, 2 parts of stearic acid, and 2 parts of carbon black;

[0147] The base material is prepared from ethylene-vinyl acetate copolymer, linear low-density polyethylene and ethylene-propylene rubber in a weight ratio of 4:1:2.

[0148] The conductor in this embodiment is made of copper wire, and the thickness of the aluminum foil layer is 0.6 mm;

[0149] The silane coupling agent is silane coupling agent KH560;

[0150] The cross-linking agent is dicumyl peroxide; the antioxidant is 2,6-di-tert-butyl-p-cresol;

[0151] The melting index of ethylene-vinyl acetate copolymer is 5.5 g / 10 min, and the mass content of vinyl acetate in ethylene-vinyl acetate copolymer is 37.5%; the melting index of ethylene-propylene rubber is 3.5 g / 10 min; and the melting index of linear low-density polyethylene is 12.5 g / 10 min.

[0152] The preparation method of the effect-enhancing agent based on flaky talcum powder adjustment in this embodiment is:

[0153] S01: Stir and mix the flaky talc powder in a sufficient amount of 5% potassium permanganate solution, then filter and dry;

[0154] The dried flaky talc, the sodium dodecylbenzene sulfonate solution and the phosphate buffer solution are mixed in a weight ratio of 2:5:1 to obtain a flaky talc agent;

[0155] S02: 2 parts of nano silica sol, 3.5 parts of carboxymethyl cellulose and 5 parts of ethanol solvent are mixed to obtain an additive solution;

[0156] The liquid and talc powder are added in a weight ratio of 2:5 and subjected to ultrasonic modification. After the ultrasonic modification is completed, the talc powder is filtered and dried to obtain a talc powder modifier.

[0157] S03: The flaky talc modifier and the synergist are mixed in a weight ratio of 7:5 and ball-milled at a speed of 1500 r / min for 2 h. After the ball-milling is completed, the mixture is washed with water and dried to obtain a synergist adjusted based on the flaky talc.

[0158] The mass fraction of the sodium dodecylbenzenesulfonate solution in this embodiment is 5.5%; the pH value of the phosphate buffer solution is 5.2.

[0159] The ultrasonic power of the ultrasonic modification treatment in this embodiment is 500 W, and the ultrasonic time is 25 min.

[0160] The effective synergistic agent of this embodiment includes the following raw materials in parts by weight:

[0161] 12.5 parts of nano-mica powder, 3.5 parts of chitosan solution, 2 parts of yttrium oxide, 3 parts of silicon carbide whiskers and 4.5 parts of sodium lignin sulfonate solution.

[0162] The mass fraction of the chitosan solution in this embodiment is 2-5%; the mass fraction of the sodium lignin sulfonate solution is 4-7%.

[0163] Preparation method of the tonic and tonifying agent of this embodiment:

[0164] S11: treating the glass fiber with proton irradiation, the irradiation power is 370 W, the irradiation time is 15 min, and the irradiation is completed to obtain irradiated glass fiber;

[0165] S12: 5.5 parts of irradiated glass fiber, 3.5 parts of 5% by mass lanthanum nitrate solution, 2 parts of urea, 1.5 parts of silane coupling agent KH550 and 4 parts of 7% by mass sodium citrate solution are fully mixed to obtain a glass fiber modified solution;

[0166] S13: immersing the hydroxyapatite in a sufficient amount of sodium silicate solution with a mass fraction of 6%, filtering and drying after the immersion is completed to obtain dry hydroxyapatite, and mixing the dry hydroxyapatite and the glass fiber modified liquid in a weight ratio of 5:3 for ball milling. After the ball milling is completed, filtering and drying are performed to obtain a replenishing and tonifying agent.

[0167] The immersion power of the immersion treatment in this embodiment is 370W, and the immersion time is 15min; the ball milling speed of the mixed ball milling treatment is 1250r / min, and the ball milling is 2h.

[0168] A method for preparing a 6A double aluminum foil shielded network cable in this embodiment includes the following steps:

[0169] Step 1: The base material, the effect agent adjusted based on flaky talc, the silane coupling agent, the tonic agent, the crosslinking agent, the antioxidant, the stearic acid and the carbon black are uniformly blended, and then kneaded at 110° C. for 5 minutes, and then extruded and granulated in a twin-screw extruder at an extrusion temperature of 135° C. to obtain a modified polymer material;

[0170] Step 2: An insulating layer and an outer sheath are made of modified polymer materials, and a core wire is made of a conductor and an insulating layer wrapped around the conductor, and each twisted pair is made of two core wires twisted together and a shielding layer wrapped around the two core wires in sequence;

[0171] Step three: a cable body is formed by making multiple twisted pairs contact each other and multiple twisted pairs contact the ground wire, a total shielding layer is covered on the periphery of the cable body, and an outer sheath is arranged on the periphery of the total shielding layer to form the 6A double aluminum foil shielded network cable of the present invention.

[0172] Comparative Example 1.

[0173] The difference from Example 3 is that no flaky talc-based enhancer is added.

[0174] Comparative Example 2.

[0175] The difference from Example 3 is that no additive liquid was added during the preparation of the enhancement agent based on flaky talc.

[0176] Comparative Example 3.

[0177] The difference from Example 3 is that the medium talc powder is prepared based on the effector adjusted by flaky talc powder and flaky talc powder is used instead.

[0178] Comparative Example 4.

[0179] The difference from Example 3 is that no synergistic agent was used in the preparation of the synergistic agent based on flaky talc.

[0180] Comparative Example 5.

[0181] The difference from Example 3 is that no tonic agent is added.

[0182] Comparative Example 6.

[0183] The difference from Example 3 is that no dry hydroxyapatite is added in the preparation of the tonic agent.

[0184] Comparative Example 7.

[0185] The difference from Example 3 is that the dried hydroxyapatite is not treated with a sodium silicate solution.

[0186] Comparative Example 8.

[0187] The difference from Example 3 is that the glass fiber modification liquid treatment is not used in the preparation of the tonic agent.

[0188] Comparative Example 9.

[0189] The difference from Example 3 is that no irradiated glass fiber is added to the glass fiber modification liquid.

[0190] Comparative Example 10.

[0191] The difference from Example 3 is that no lanthanum nitrate solution and silane coupling agent KH550 are added to the glass fiber modification liquid.

[0192] The products of Examples 1-3 and Comparative Examples 1-10 were tested for mechanical properties and attenuation properties under normal conditions, placed at -5°C for 12 hours, and then placed under 2% hydrochloric acid mist for 24 hours. The test was repeated 10 times to test the cold resistance and corrosion resistance stability of the products. The performance measurement results are as follows

[0193]

[0194]

[0195] It is concluded from Examples 1-3 and Comparative Examples 1-10 that

[0196] The product of Example 3 of the present invention has excellent tensile strength, elongation at break, and attenuation constant, and the mechanical properties and attenuation stability of the product can be improved in a coordinated manner. At the same time, the cold resistance and corrosion resistance stability of the product are remarkable.

[0197] If the product does not contain any of the talcum powder-based synergist or the tonic agent, the product's performance will be significantly worse. The synergistic effect of the two agents will be the most obvious.

[0198] In the preparation of the effective agent based on flaky talc, no additive liquid was added, in the preparation of the effective agent based on flaky talc, flaky talc was used to replace the talc powder, and in the preparation of the effective agent based on flaky talc, no effective co-adjuvant was used. The performance of the product showed a trend of deterioration. At the same time, the performance of the product was significantly deteriorated when no effective co-adjuvant was used.

[0199] In the preparation of the replenishing and restoring agent, no dried hydroxyapatite was added, the dried hydroxyapatite was not treated with a sodium silicate solution, the glass fiber modifying liquid was not treated in the preparation of the replenishing and restoring agent, no irradiated glass fiber was added to the glass fiber modifying liquid, and no lanthanum nitrate solution or silane coupling agent KH550 was added to the glass fiber modifying liquid. The performance of the products showed a trend of deterioration to varying degrees. The replenishing and restoring agent made of the glass fiber modifying liquid obtained by the method of the present invention and the dried hydroxyapatite of the present invention had the most significant performance effect. Other methods were not as obvious as the effect of the present invention.

[0200] Based on the above tests, the present invention finds that the synergistic agent has a greater impact on the performance of the product. Based on this, the present invention further explores it.

[0201] Experimental example 1.

[0202] The only difference from Example 3 is that no nano mica powder is added to the synergistic agent.

[0203] Experimental example 2.

[0204] The only difference from Example 3 is that yttrium oxide is not added to the synergistic agent.

[0205] Experimental Example 3.

[0206] The only difference from Example 3 is that no sodium lignin sulfonate solution is added to the synergist.

[0207] Experimental Example 4.

[0208] The only difference from Example 3 is that silicon carbide whiskers are not added to the synergistic agent.

[0209] Experimental Example 5.

[0210] The only difference from Example 3 is that no chitosan solution is added to the synergistic agent.

[0211]

[0212] It can be seen from Experimental Examples 1-5 that when no nano-mica powder is added to the effective synergist, the performance change trend of the product is the largest, followed by when no silicon carbide whiskers are added. Silicon carbide whiskers and nano-mica powder play a leading role in the effective synergist, while when no yttrium oxide, sodium lignin sulfonate solution, or chitosan solution is added to the effective synergist, the performance of the product tends to deteriorate. The addition of yttrium oxide, chitosan solution, and sodium lignin sulfonate solution can coordinate with silicon carbide whiskers and nano-mica powder to jointly enhance the performance effect of the product. The performance effects of the effective synergists obtained by different methods tend to deteriorate, and only the effective synergist obtained by the method of the present invention has the most significant performance effect.

[0213] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

[0214] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A 6A double aluminum foil shielded network cable, characterized in that: The shielded network cable comprises a cable body, and the cable body comprises a plurality of twisted pairs of wires; Each twisted pair includes two core wires twisted together and a shielding layer wrapped around the two core wires; each core wire includes a conductor and an insulating layer wrapped around the conductor; The cable body also includes a ground wire, and on a cross section of the cable body, the plurality of twisted pairs are evenly distributed around the ground wire; the plurality of twisted pairs are in contact with each other, and the plurality of twisted pairs are in contact with the ground wire; Also included is an overall shielding layer wrapped around the periphery of the cable body; The shielding layer and the overall shielding layer are both aluminum foil layers; the network cable also includes an outer sheath wrapped around the outer periphery of the overall shielding layer; The insulating layer and the outer sheath are both made of modified polymer materials, wherein the modified polymer materials include the following raw materials in parts by weight: 35-45 parts of base material, 7-11 parts of an improving agent based on flaky talc, 3-7 parts of a silane coupling agent, 4-6 parts of a replenishing and improving agent, 1-3 parts of a crosslinking agent, 2-5 parts of an antioxidant, 1-3 parts of stearic acid, and 1-3 parts of carbon black; The base material is prepared from ethylene-vinyl acetate copolymer, linear low-density polyethylene, and ethylene-propylene rubber in a weight ratio of 4:1:2; The preparation method of the effect-enhancing agent based on flaky talcum powder is as follows: S01: Stir and mix the flaky talc powder thoroughly in a sufficient amount of 5% potassium permanganate solution, then filter and dry; The dried flaky talc, the sodium dodecylbenzene sulfonate solution and the phosphate buffer solution are mixed in a weight ratio of 2:5:1 to obtain a flaky talc agent; S02: 1-3 parts of nano silica sol, 2-5 parts of carboxymethyl cellulose and 4-6 parts of ethanol solvent are mixed to obtain an additive solution; The additive liquid and the flaky talc powder agent were subjected to ultrasonic modification treatment in a weight ratio of 2:5, and after the ultrasonic treatment was completed, the flaky talc powder agent was filtered and dried to obtain the flaky talc powder modifier; S03: The flaky talc modifier and the synergist are mixed and ball-milled in a weight ratio of 7:5, with a ball-milling speed of 1500 r / min for 2 h. After the ball-milling is completed, the mixture is washed with water and dried to obtain a synergist adjusted based on the flaky talc; The effective synergist comprises the following raw materials in parts by weight: 10-15 parts of nano-mica powder, 2-5 parts of chitosan solution, 1-3 parts of yttrium oxide, 2-4 parts of silicon carbide whiskers and 3-6 parts of sodium lignin sulfonate solution; The preparation method of the tonic and tonifying agent: S11: treating the glass fiber with protons, wherein the irradiation power is 350-400 W, the irradiation time is 10-20 min, and the irradiation is completed to obtain irradiated glass fibers; S12: fully blending 4-7 parts of irradiated glass fiber, 2-5 parts of 5% by mass lanthanum nitrate solution, 1-3 parts of urea, 1-2 parts of silane coupling agent KH550 and 3-5 parts of 7% by mass sodium citrate solution to obtain a glass fiber modified solution; S13: immersing the hydroxyapatite in a sufficient amount of sodium silicate solution with a mass fraction of 5-7%, filtering and drying after the immersion is completed to obtain dry hydroxyapatite, and mixing the dry hydroxyapatite and the glass fiber modified liquid in a weight ratio of 5:3 for ball milling. After the ball milling is completed, filtering and drying are performed to obtain a replenishing and tonifying agent.

2. A 6A double aluminum foil shielded network cable according to claim 1, characterized in that: The conductor is made of copper wire, and the thickness of the aluminum foil layer is 0.5-0.7 mm; The silane coupling agent is silane coupling agent KH560; The cross-linking agent is dicumyl peroxide; the antioxidant is 2,6-di-tert-butyl-p-cresol; The melt index of ethylene-vinyl acetate copolymer is 4-7 g / 10 min, and the mass content of vinyl acetate in ethylene-vinyl acetate copolymer is 35-40%; the melt index of ethylene-propylene rubber is 2-5 g / 10 min; and the melt index of linear low-density polyethylene is 10-15 g / 10 min.

3. A 6A double aluminum foil shielded network cable according to claim 2, characterized in that: The mass fraction of the sodium dodecylbenzene sulfonate solution is 4-7%; the pH value of the phosphate buffer solution is 5.0-5.

5.

4. The 6A double aluminum foil shielded network cable according to claim 3, characterized in that: The ultrasonic power of the ultrasonic modification treatment is 450-550W, and the ultrasonic time is 20-30min.

5. A 6A double aluminum foil shielded network cable according to claim 4, characterized in that: The mass fraction of the chitosan solution is 2-5%; the mass fraction of the sodium lignin sulfonate solution is 4-7%.

6. The 6A double aluminum foil shielded network cable according to claim 5, characterized in that: The immersion power of the immersion treatment is 350-400W, and the immersion time is 10-20min; the ball milling speed of the mixed ball milling treatment is 1000-1500r / min, and the ball milling is 2h.

7. A method for preparing a 6A double aluminum foil shielded network cable as claimed in any one of claims 1 to 6, characterized in that: The following steps are involved: Step 1: The base material, the effect agent adjusted based on flaky talc, the silane coupling agent, the tonic agent, the crosslinking agent, the antioxidant, the stearic acid and the carbon black are uniformly blended, and then kneaded at 110° C. for 5 minutes, and then extruded and granulated in a twin-screw extruder at an extrusion temperature of 135° C. to obtain a modified polymer material; Step 2: An insulating layer and an outer sheath are made of modified polymer materials, and a core wire is made of a conductor and an insulating layer wrapped around the conductor, and each twisted pair is made of two core wires twisted together and a shielding layer wrapped around the two core wires in sequence; Step 3: A cable body is formed by making multiple twisted pairs contact each other and multiple twisted pairs contact the ground wire, and a total shielding layer is covered on the periphery of the cable body. An outer sheath is arranged on the periphery of the total shielding layer to form the 6A double aluminum foil shielded network cable.

Citation Information

Patent Citations

  • Network cable

    CN211237808U

  • Corrosion-resistant double-shielding-layer seven-category network cable

    CN216980218U